Maximizing Rootstock Seed Production - Alferez, Fernando; de Carvalho, Deived U; Boakye, Daniel A; Gast, Tim; Dutt, Manjul (EDIS, 2021)
This article covers new appraches to ensure better yields of seeds from highly sought-after rootstocks, including US942 and US897. Since harvesting is done typically in fall, after hurricane season has peaked, chances are that a hurricane can impact seed availability for producing liners. We have developed a sysrem to assess seed maturity, so seeds can be harvested as soon as they are viable; this means harvesting earlier in the year, and hence allowing us to play around hurricane season, increasing seed yield.